Multinational maids: Stepwise migration in a global labor market - Paul, Anju Mary (New York Cambridge University press, 2017)
Multinational Maids offers an in-depth investigation into the international migrations of Filipino and Indonesian migrant domestic workers. The author taps on her rigorous study of more than 1,200 subjects' migration trajectories to reveal how these migrants work in a series of overseas countries to improve their lives and, in some cases, seek permanent residence in another country. Challenging the portrayal of Asian migrant domestic workers as victims of globalization, Multinational Maids reveals migrants' agency and strategic thinking under conditions of constraint.